Development of an automatic LSM recognition system for mobile devices - Mendoza-Tene, J.L.; Fajardo-Delgado, D.; Fajardo-Flores, S.B.; Puga-Nathal, M.E.; Sánchez-Cervantes, M.G. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
This paper explores the effectiveness of using mobile devices for the automatic recognition of both static and dynamic signs in Mexican Sign Language (LSM). This is due to the fact that most current works on LSM recognition typically focus on one type of sign (static or dynamic) and often involve specialized devices beyond the reach of the general population. To conduct this study, a solution was implemented, consisting of an Android application for capturing videos and sending them to a cloud-based web service hosting an automatic recognition system. The system employs the Dynamic Time Warping (DTW) algorithm to compare the features of the received video with those of a set of videos categorized by sign. It is noteworthy that this work is the first to use DTW for static signs in LSM. Finally, an experimental study of the system’s performance was conducted using three mobile devices with different capabilities for both video capture and processing. Results indicate that, while camera quality affects recognition efficiency, it is not a decisive factor. Additionally, due to the video characterization method and LSM-specific attributes, the system tends to recognize static signs better than dynamic ones, even when using DTW.